cAMP Response Element-Binding Protein in the Amygdala Is Required for Long- but not Short-Term Conditioned Taste Aversion Memory - Lamprecht, Raphael (J Neurosci, 1997)
In conditioned taste aversion (CTA) organisms learn to avoid a taste if the first encounter with that taste is followed by transient poisoning. The neural mechanisms that subserve this robust and long-lasting association of taste and malaise have not yet been elucidated, but several brain areas have been implicated in the process, including the amygdala. In this study we investigated the role of amygdala in general, and the cAMP response element-binding protein (CREB) in the amygdala in particular, in CTA learning and memory. Toward that end, we combined antisense technology in vivo with behavioral, molecular, and histochemical analysis. Local microinjection of phosphorothioate-modified oligodeoxynucleotides (ODNs) antisense to CREB into the rat amygdala several hours before CTA training transiently reduced the level of CREB protein during training and impaired CTA memory when tested 3–5 d later. In comparison, sense ODNs had no effect on memory. The effect of antisense was not attributable to differential tissue damage and was site-specific. CREB antisense in the amygdala had no effect on retrieval of CTA memory once it had been formed, and did not affect short-term CTA memory. We propose that the amygdala, specifically the central nucleus, is required for the establishment of long-term CTA memory in the behaving rat; that the process involves long-term changes, subserved by CRE-regulated gene expression, in amygdala neurons; and that the amygdala may retain some CTA-relevant information over time rather than merely modulating the gustatory trace during acquisition of CTA.